KHALIL GIBRAN’S PHILOSOPHICAL POETRY: A MODERNIST VOICE IN ARABIC LITERATURE - Bhat, Kaffeel Ahmad; Baba, Rayees Ahmad (ShodhKosh: Journal of Visual and Performing Arts, 2024)
This paper looks at the philosophical ideas in Khalil Gibran’s poetry, recognizing him as an important modern voice in Arabic literature. Gibran, who combined Eastern mysticism with Western ideas of individualism, changed Arabic poetry by introducing themes like existentialism, spirituality, and personal freedom. His poems, full of deep reflection and symbolism, moved away from traditional Arabic poetry by using free verse and a more personal style. This study explores how Gibran’s thoughts on life, death, love, and the self make his poetry a way to explore intellectual and spiritual ideas. It also examines how Gibran challenged strict social and religious norms, promoting freedom of the individual and self-discovery. Through a detailed analysis of his key poems, the paper highlights Gibran’s role in shaping modern Arabic literature and his influence on both Arabic and global literary thought. By placing Gibran’s poetry within the context of modernist literature, this study emphasizes his importance as a key figure who helped transform Arabic poetry in the 20th century.